2021
DOI: 10.1136/gutjnl-2020-322873
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A–specific deficiency induces spontaneous inflammation specifically in the ileum

Abstract: ObjectiveAlthough immunoglobulin A (IgA) is abundantly expressed in the gut and known to be an important component of mucosal barriers against luminal pathogens, its precise function remains unclear. Therefore, we tried to elucidate the effect of IgA on gut homeostasis maintenance and its mechanism.DesignWe generated various IgA mutant mouse lines using the CRISPR/Cas9 genome editing system. Then, we evaluated the effect on the small intestinal homeostasis, pathology, intestinal microbiota, cytokine production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Pigr -/mice, deficient in SIgA and SIgM, display significant degradation of the gut epithelial barrier, as reflected by the leakage of serum proteins and elevated concentrations of fecal albumin [12], lower cecal microbial diversity, and higher susceptibility to dextran sulfate sodium (DSS)-induced colitis compared with wild-type (WT) mice [13]. Mice with selective IgA deficiency (IghA -/-) also host a less diverse microbiota compared with WT littermates, suggesting an important role for IgA in regulating intestinal microbiota and homeostasis [14].…”
Section: New Insights Regarding Sig Functions In the Intestinal Lumen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pigr -/mice, deficient in SIgA and SIgM, display significant degradation of the gut epithelial barrier, as reflected by the leakage of serum proteins and elevated concentrations of fecal albumin [12], lower cecal microbial diversity, and higher susceptibility to dextran sulfate sodium (DSS)-induced colitis compared with wild-type (WT) mice [13]. Mice with selective IgA deficiency (IghA -/-) also host a less diverse microbiota compared with WT littermates, suggesting an important role for IgA in regulating intestinal microbiota and homeostasis [14].…”
Section: New Insights Regarding Sig Functions In the Intestinal Lumen...mentioning
confidence: 99%
“…Indeed, IgG-, IgM-, and IgA-bound bacteria are significantly increased in the feces of patients with IBD compared with healthy controls, and high IgG and IgA bacterial coatings have correlated with CD activity [70,71]. Furthermore, SIgAD is a risk factor for IBD in humans [72] and Igha -/mice display exacerbated colitis [14], reinforcing the importance of IgA in shaping a diverse microbiota and, thus, limiting IBD onset. However, several observations also suggest a detrimental role of increased Ig production in maintaining a state of inflammation.…”
Section: Trends Trends In In Immunology Immunologymentioning
confidence: 99%
“…These feeds were standardized at a salt content of 1.4 w/w%. IL-22 deficient mice were generated by a genome editing system of the CRISPR/Cas9 as described previously [17]. A transgenic mouse line expressing YC3.60 for intravital imaging was described previously [18].…”
Section: Cells and Micementioning
confidence: 99%
“…Another metagenomic study demonstrated that SIgAD patients had reduced microbial diversity but were enriched with opportunistic bacteria like Escherichia coli [130]. As with humans, the mouse model of IgA deficiency (IgA −/− ) resulted in spontaneous inflammation specifically in the ileum, and segmented filamentous bacteria (SFB) were noted to bloom in IgA −/− mice within the inherited dysbiotic microbiota [131]. As studies linking SIgAD and the gut microbiota are only a few years old, more research is needed to uncover what effects these have on the autoimmune disease progression.…”
Section: Iga Deficiency In Autoimmunitymentioning
confidence: 99%